Genetic variation and radiation quality impact cancer promoting cellular phenotypes in response to HZE exposure. (February 2019) - Sridharan, Deepa M.; Enerio, Shiena; Wang, Chris; LaBarge, Mark A.; Stampfer, Martha R.; Pluth, Janice M.
Abstract: There exists a wide degree of genetic variation within the normal human population which includes disease free individuals with heterozygote defects in major DNA repair genes. A lack of understanding of how this genetic variation impacts cellular phenotypes that inform cancer risk post heavy ion exposure poses a major limitation in developing personalized cancer risk assessment astronauts. We initiated a pilot study with Human Mammary Epithelial Cell strains (HMEC) derived from wild type, a p16 silenced derivative of wild type, and various genetic variants that were heterozygote for DNA repair genes; BRCA1, BRCA2 and ATM. Cells strains were exposed to different high and low LET radiation qualities to generate both simple and complex lesions and centrosome aberrations were examined as a surrogate marker of genomic instability and cancer susceptibility post different exposures. Our results indicate that centrosome aberration frequency is higher in the genetic variants under study. The aberration frequency increases with dose, complexity of the lesion generated by different radiation qualities and age of the individual. This increase in genomic instability correlates with elevated check-point activation post radiation exposure. These studies suggest that the influence of individual genetics on cell cycle regulation could modify the degree of early genomic instability in response to complex lesions and potentially define cancer predisposition in response to HZE exposure. These results will have significant implications in estimating cancer susceptibility in genetically variant individuals exposed to HZE particles.